Lyn Bakery, Kafe & Katering - Abdul, Mohani; Hashim, Haslina; Mahadi, Ahmad Marwan; Muftar, Siti Raihan; Shukor, Farhah Izzati; Othman, Amanina Awis; Rajendran, Parthiban (Universiti Putra Malaysia Press, 2011)
This case presents a typical start-up SME. It provides critical scenarios whereby the owner was desperately in need to get her loan approved by the SME Corp so that she could invest in modern technology, that would enable her to churn out the company’s products at a much higher volume per period and compete with her established competitors. However, the loan approval was still pending due to unsatisfactory business accounts reporting. Thus it provides trainees opportunities to analyze and evaluate this case and come up with reports to help Roslina get her loan application documents considered favorably.